Seroprevalence of Babesia bovis and Babesia bigemina in cattle in the Soutpansberg region, Limpopo Province, South Africa, associated with changes in vector-tick populations - M.H. Tønnesen (Journal of the South African Veterinary Association, 2006)
A survey was conducted at 30 communal dip tanks and on 5 commercial farms in Limpopo Province, South Africa, during 1999 and 2000 to determine the seroprevalence of antibodies to Babesia bovis and Babesia bigemina. Cattle seropositive for B. bovis were found in 97 % of the herds on communal land; the overall seroprevalence changed little between 1999 (63.3 %) and 2000 (62.4 %). All herds surveyed were infected with B. bigemina, and overall seroprevalence decreased significantly from 56.1 % in 1999 to 49.3 % in 2000. In herds on communal land in Sour Lowveld Bushveld, overall seroprevalence of B. bovis increased from 70 % in 1999 to 80 % in 2000, while seroprevalence of B. bigemina decreased from 70 % in 1999 to 30 % in 2000. This was possibly due to an influx of Rhipicephalus (Boophilus) microplus that occurred at the time. In commercially farmed herds the seroprevalence to B. bovis increased significantly from 19 % in 1999 to 57.5 % in 2000. All commercial herds in the survey tested positive to B. bigemina, with a seroprevalence of 48.3 % in 1999 and 47.5 % in 2000. During 1999, cattle in 60 % of the dip tank / farm herds with only R. (B.) microplus present were approaching endemic stability to both B. bovis and B. bigemina. In 2000, 60 % of the herds with only R. (B.) microplus present were approaching endemic stability for B. bovis, while only 45 % were approaching endemic stability for B. bigemina. Those dip tanks / farms where only R. (B.) microplus was recorded had a significantly higher seroprevalence of B. bovis than those where both tick species were present.